Reconceptualizing Assessment in Local Content Education: Developing a Qualitative Assessment Framework through Community-Based Cultural Learning - Hadiyatno, Hadiyatno; Jazuli, Muhammad; Syakir, Syakir; Djatiprambudi, Djuli (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2026)
Objective: This study aims to develop and conceptualize a qualitative assessment framework for local content education by examining how community-based cultural learning practices inform the construction and evaluation of assessment processes. It addresses the limitations of conventional assessment practices that emphasize surface recognition, product-based outcomes, and cognitive recall, while overlooking interpretative and reflective dimensions of learning. Method: This study employed a qualitative case study involving senior high school students, teachers, and cultural practitioners engaged in Cirebon mask learning. Data were collected through observation, in-depth interviews, and documentation, and analyzed using thematic analysis to identify patterns of learning and emerging assessment practices. Results: The findings reveal that students’ learning is characterized by engagement, interpretative dialogue, and reflective meaning-making. Assessment emerges through interaction and participation rather than functioning as a predefined measurement system, indicating a misalignment between experiential learning processes and established assessment practices. Novelty: This study proposes a qualitative assessment framework consisting of recognition, interpretation, and reflection. The framework reconceptualizes assessment as an emergent, interpretative, and context-sensitive process, while also providing a basis for evaluating existing assessment practices beyond surface-level and product-oriented approaches in culturally grounded learning environments.